2005
DOI: 10.1016/j.nbd.2005.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Reduced hippocampal neurogenesis in R6/2 transgenic Huntington's disease mice

Abstract: We investigated whether cell proliferation and neurogenesis are altered in R6/2 transgenic Huntington's disease mice. Using bromodeoxyuridine (BrdU), we found a progressive decrease in the number of proliferating cells in the dentate gyrus of R6/2 mice. This reduction was detected in pre-symptomatic mice, and by 11.5 weeks, R6/2 mice had 66% fewer newly born cells in the hippocampus. The results were confirmed by immunohistochemistry for the cell cycle markers Ki-67 and proliferating cell nuclear antigen (PCNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
108
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(126 citation statements)
references
References 58 publications
16
108
2
Order By: Relevance
“…Several studies have reported reduced progenitor proliferation rates in the DG in both mouse models (the slower progressing R6/1 line) (Lazic et al 2004(Lazic et al , 2006 and R6/2 mice with a fast disease progression (Gil et al 2004(Gil et al , 2005Phillips et al 2005;Kohl et al 2007). This resulted in a reduction of newly generated neurons, although, in most reports, neuronal differentiation was not compromised.…”
Section: Adult Neurogenesis In Transgenic Animal Models Of Hdmentioning
confidence: 99%
“…Several studies have reported reduced progenitor proliferation rates in the DG in both mouse models (the slower progressing R6/1 line) (Lazic et al 2004(Lazic et al , 2006 and R6/2 mice with a fast disease progression (Gil et al 2004(Gil et al , 2005Phillips et al 2005;Kohl et al 2007). This resulted in a reduction of newly generated neurons, although, in most reports, neuronal differentiation was not compromised.…”
Section: Adult Neurogenesis In Transgenic Animal Models Of Hdmentioning
confidence: 99%
“…There are contrasting reports in neurogenesis between HD human brains and mouse models (Phillips et al, 2006;Phillips et al, 2005;Grote et al, 2005;Gil et al, 2005;Tattersfield et al, 2005;Lazic et al, 2004;Curtis et al, 2003). For example, reduced neurogenesis has been reported in R6/2 mice (Phillips et al, 2006;Phillips et al, 2005;Gil et al, 2005), but in humans, there was increased proliferation and neurogenesis (Curtis et al, 2003).…”
Section: Sertraline Increases Basal Neurogenesis In Hippocampus and Smentioning
confidence: 99%
“…These studies suggest that increasing BDNF levels is beneficial in HD. Altered neurogenesis has been reported in HD mouse models and in human postmortem brains (Phillips et al, 2006;Phillips et al, 2005;Grote et al, 2005;Gil et al, 2005;Lazic et al, 2004;Curtis et al, 2003). In addition to promoting neuronal survival, BDNF also regulates neurogenesis (Duman, 2004;Cotman and Berchtold 2002).…”
Section: Introductionmentioning
confidence: 99%
“…11,80,119,150 The microenvironment plays a key role in maintaining the neurogenic potential of the adult brain; 19,117,136 it also plays a role in the fate restriction of endogenous NSCs in neurogenic regions. 95,137,145 Abnormalities in adult neurogenesis as exhibited in both HD transgenic mice 63,64,89,90,124,146 and humans 35-37 may have clinical relevance for patients afflicted with HD. Although striatal pathophysiology contributes to some motor and cognitive defects in patients with HD, 5 nonstriatal pathology, especially of the hippocampus, may mediate aspects of affective and cognitive deficits in HD.…”
Section: Fig 2 Drawing Illustrating Therapies In Hdmentioning
confidence: 99%
“…Although striatal pathophysiology contributes to some motor and cognitive defects in patients with HD, 5 nonstriatal pathology, especially of the hippocampus, may mediate aspects of affective and cognitive deficits in HD. 35,121,131 Neural progenitor cell proliferation, survival, and structure are abnormal in the DG of mice transgenic for the human HD gene, 63,64,89,90,124 an effect that can be partially restored by environmental enrichment. 90 Environmental enrichment or physical activity, which modulates the proliferation and survival of newly formed neurons, improves motor and cognitive deficits in HD transgenic mice models.…”
Section: Fig 2 Drawing Illustrating Therapies In Hdmentioning
confidence: 99%